Extraction, Structures, Bioactivities and Structure-Function Analysis of the Polysaccharides From Safflower (Carthamus tinctorius L.) - Wu, Xiaoyi; Cai, Xinbo; Ai, Jiaxuan; Zhang, Chi; Liu, Nan; Gao, Wei (Frontiers in Pharmacology, 2021)
Safflower (Carthamus tinctorius L.) is a herbal plant with a long history of clinical application worldwide, such as coronary heart disease, hypertention, dysmenorrhea and amenorrhea. It is also extensively used as an important oilseed plant for hundreds of years in some countries, like China, India, Mexico and the United States. Therefore, safflower is believed as a crop with dual values of medicine and economy as well. Safflower polysaccharide (SPS), from the plant, is believed as one of the most important biologically active components with multiple pharmacological properties, including anti-tumor, immune regulation, anti-oxidation, and anti-cerebral ischemia reperfusion injury effects. The polysaccharide, from bee pollen of safflower, named PBPC, also attracts the attention of researchers because of its particular origin and bioactivities. Although the extraction, purification, structure and biological activities of SPS and PBPC have been studied for decades, there is not any available review both concerning SPS and PBPC. In this condition, this paper aims to systematically review the research progress in extraction, purification, structural characteristics, and bioactivities of SPS and PBPC, and provide basis for the in-depth study about their structure-bioactivity relationship. It will serve as a methodological outline for further research in fields of new drug discovery and clinical application of SPS or PBPC, and simultaneously remind us of unresolved problems noted in the polysaccharide research.